Comparison of various FEM approaches in analysis of passive earth pressures - Pecník, Miroslav; Borzovič, Viktor (Computer Assisted Methods in Engineering and Science, 2017)
Passive earth pressure is an important element in integral bridge design. Due to the integral connection between bridge deck and abutments, the integral bridge expansion and contraction under temperature action causes abutments to move together with the deck.With temperature varying in time, this also causes varying earth pressures acting on the abutments. Abutments are generally being designed to withstand passive earth pressure because it is significantly higher than active earth pressure. However, by using the controlled yielding technique, these pressures can be considerably lowered. For this purpose, a few-centimeters-thick layer of easily compressible material is placed behind abutment, which provides a means to potential material saving. In this article, results from 2D and 3D FEM models of integral abutment are presented. Internal forces obtained in 2D and 3D analysis are compared between themselves, and influence of compressible layer thickness on internal forces is also presented.